The Use Indonesian Deixis in The Banten’s Folklore Book 2 By Endang Firdaus - Zulfa Azhari Ghozali, Muhammad; Agnistiana, Estri; Syahfarezi, Garin (International Proceedings of Nusantara Raya, 2023)
This study aims to describe the forms of person deixis, time deixis, and social deixis in the book People's Stories from Banten 2 by Endang Firdaus. This research is a qualitative Banten’s Folklore Book 2 by Endang Firdaus descriptive research. The data source in this study Banten’s Folklore Book 2 by Endang Firdaus which contains the use of deixis. In the Banten’s Folklore Book 2 by Endang contains several folk tales originating from Banten. The form of deixis found is speech or storytelling in written language in the Banten’s Folklore Book 2 by Endang Firdaus. The data collection technique in this study used the listen method with the basic technique of tapping and note-taking techniques as an advanced technique. The research instrument used in this study was the researcher himself (human instrument). Data analysis in this study used the equivalent method. The equivalence method used in this research is the referential subtype equivalence method. Based on the results of data analysis, it was found that there were 15 pieces of data in the form of personal deixis, time deixis, and social deixis in the Banten’s Folklore Book 2 by Endang Firdaus, namely (1) 7 pieces of personal deixis; (2) anaphora deixis 4 pieces of data; (3) as many as 1 forms of cataphoric deixis; (4) as many as 1 pieces of time deixis data; and (5) as many as 2 pieces of data form social deixis. Based on these results, the most dominant form of deixis data found in the Banten’s Folklore Book 2 by Endang is anaphora deixis in the form of persona.